SEBARAN GANGGUAN NEUROPSIKIATRI PADA STAF MEDIK NEUROLOGI SELAMA PANDEMI COVID19 - Rini Nindela,* Yunni Diansari,* Sri Handayani,* Selly Marisdina,* Bintang Arroyantri Prananjaya** (NEURONA, 2020)
INTRODUCTION CORONA VIRUS DISEASE2019 COVID19 IS A NEW DISEASE DESIGNATED AS A GLOBAL PANDEMIC BY WHO AFTER CAUSING A LARGE NUMBER OF DEATHS IN A SHORT PERIOD OF TIME IN VARIOUS PARTS OF THE WORLD THE COVID19 PANDEMIC HAS NOT ONLY CAUSED PHYSICAL IMPACTS BUT ALSO MENTAL FATIGUE ON THE COMMUNITY ESPECIALLY HEALTH WORKERS AS THE FRONTLINE IN HANDLING COVID19